2016
DOI: 10.1002/ana.24749
|View full text |Cite
|
Sign up to set email alerts
|

Infantile spasms in down syndrome: Rescue by knockdown of the GIRK2 channel

Abstract: The GABAB R-coupled GIRK2 channel is necessary for the GABAB R agonist-induced infantile spasms phenotype in the Ts mouse and may represent a novel therapeutic target for the treatment of infantile spasms in DS. Ann Neurol 2016;80:511-521.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Another gene that has been linked to DS is Kcnj6 , which encodes potassium-voltage-gated channel subfamily J member 6. This gene has been shown to contribute to CHDs ( Lignon et al, 2008 ) and to cognitive defects, together with another gene not yet identified ( Jiang et al, 2015 ; Joshi et al, 2016 ; Cooper et al, 2012 ). The gene encoding cystathionine β-synthase ( Cbs ), which is involved in the methionine/cysteine cycle, is overexpressed in the DS brain ( Ichinohe et al, 2005 ).…”
Section: Identification Of Molecular Mechanisms and Candidate Genes Fmentioning
confidence: 99%
“…Another gene that has been linked to DS is Kcnj6 , which encodes potassium-voltage-gated channel subfamily J member 6. This gene has been shown to contribute to CHDs ( Lignon et al, 2008 ) and to cognitive defects, together with another gene not yet identified ( Jiang et al, 2015 ; Joshi et al, 2016 ; Cooper et al, 2012 ). The gene encoding cystathionine β-synthase ( Cbs ), which is involved in the methionine/cysteine cycle, is overexpressed in the DS brain ( Ichinohe et al, 2005 ).…”
Section: Identification Of Molecular Mechanisms and Candidate Genes Fmentioning
confidence: 99%
“…In addition, Ts65Dn mice display alterations in dendritic spine morphology (Belichenko et al, 2004; Guidi et al, 2013) and impaired neurogenesis both in the developing brain (Baxter et al, 2000; Roper et al, 2006; Chakrabarti et al, 2007, 2010; Contestabile et al, 2007, 2009) and in neurogenic niches of the adult brain (Clark et al, 2006; Bianchi et al, 2010a; Contestabile et al, 2013). Additionally, Ts65Dn mice are not spontaneously epileptic, but show increased seizures incidence in some experimental epilepsy paradigms (Cortez et al, 2009; Westmark et al, 2010; Joshi et al, 2016). Finally, similarly to DS patients, Ts65Dn mice also exhibit some sleep alterations and hyperactivity in locomotor behavior (Escorihuela et al, 1995; Reeves et al, 1995; Sago et al, 2000; Colas et al, 2008).…”
Section: Mouse Models Of Dsmentioning
confidence: 99%
“…This increase of GABA B /GIRK signaling in Ts65Dn neurons could strongly affect neuronal excitability and plasticity by enhancement of GIRK-mediated shunting inhibition, reduction of excitatory PSPs, back-propagating action potentials, and change of neuronal passive properties (Lüscher et al, 1997; Koyrakh et al, 2005). Anyhow, genetically restoring GIRK2 gene dosage to disomy in Ts65Dn mice (by crossing to GIRK2 +/− mice) rescued the observed increase in GABA B -triggered currents in CA1 pyramidal neurons (Joshi et al, 2016). In agreement with triplication of KCNJ6 and the increase of GABA B /GIRK signaling, V REST is hyperpolarized by 2.3 mV in CA1 pyramidal neurons and by 6.2 mV in DG granule cells (DGGC; Best et al, 2012; Kleschevnikov et al, 2012b).…”
Section: Gaba Signaling In Ds Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of GIRK2 is necessary for the production of the IS-like phenotype, as the knockdown of the Kcnj6 gene (which codes for GIRK2) made the mice resistant to GABA B agonist-induced spasms [42,43]. However, trisomy of Kcnj6 is not sufficient for replicating the desired phenotype.…”
Section: Excessive Gaba B Receptor-mediated Potassium Currents: Ts65dmentioning
confidence: 99%